Not updating binary sequence of periods of smooth functions of two variables by linear operators - Приставка, П.О. (Proceedings of National Aviation University (archive), 2009)
This article is the solution of practical research of the polynomial splines of two variable based on the B-splines that, on average, are related to the interpolar. These splines allow us to get simple calculating schemes which are convenient for the practical application for non-binary subdivisions.